A Conceptual Model to Support Teaching of Software Engineering Controlled (Quasi-)Experiments - Luz, Carlos; Oliveirajr, Edson; Steinmacher, Igor (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Throughout controlled experimentation, it is possible to provide evidence of the software being developed. In the academic environment, Experimentation in Software Engineering (ESE) is essential to understanding cause-effect relations, enabling a vision of the development process, and taking action on actual events in the software industry. As much as the experimentation processes have been used in industry and academia, there is a lack of formalization of the principles of ESE teaching and artifacts that can be useful to support it in higher education. One of the means to contribute to such a topic would be the design of a conceptual model, which is widely discussed in the literature, thus applying empirical methods for a better understanding of the context and representation of ESE teaching. Thus, in this paper, we developed a conceptual model to support the teaching of controlled experiments and quasi-experiments. To design the conceptual model, we carried out an analysis of metadata from controlled experiments and quasi-experiments in the literature and conducted a survey to collect data from instructors who teach ESE. We evaluated the model with the Technology Acceptance Model (TAM). Results consist of a feasible conceptual model aiming to standardize the basic concepts of ESE and further support the production and reuse of ESE materials.